Factors of Poor Glycemic Control among Individuals with Diabetes in Atbara, Sudan - Noor, Sufian K.M.; Sherif, Elssadig O.E.; Badi, Safaa; Malik, Sawazen; Mustafa, Hatim S.A.M. (Journal of Diabetes and Endocrine Practice, 2025)
Understanding of factors influencing diabetes control is crucial for effective interventions to improve glycemic control.We aimed to determine poor glycemic control in patients with type 2 diabetes (T2D) in Atbara Diabetes Centers, Sudan,An observational, cross-sectional, multicenter-based study was conducted from June to December 2023. The study included Sudanese patients with T2D attending care centers. The sample size was 385 participants by convenience sampling. Data were collected through face-to-face interviews by a structured questionnaire.The majority of the participants were between 40 and 60 years old (47.3%), female (56.4%), married (74.3%), and living in urban areas (74.8%). Patient-related factors, such as obesity (20.8%) and sedentary lifestyles (15.1%), revealed that many participants had habits and lifestyles that negatively impacted health. However, most participants had good medication adherence and awareness of diabetes control (68.6 and 53%, respectively). Many participants reported experiencing a stressful lifestyle (52.5%). Only 51.9% had well-controlled diabetes. Age, medication adherence, and diabetes awareness were significantly associated with glycemic control. Predictors of poor glycemic control included age above 60 years, poor medication adherence, poor awareness of diabetes, and not undergoing regular monitoring.Poor glycemic control is associated with inadequate self-management practices, a lack of proper education and awareness about diabetes management, limited access to healthcare services, and comorbidities. These findings should inform healthcare providers and policymakers about implementing targeted interventions to address the specific needs of individuals with T2D. By addressing these factors and implementing effective interventions, it is possible to enhance glycemic control and ultimately improve the overall health outcomes of this population.
Keywords: glycemic control; diabetes; diabetes centers; assessment; Sudan